PERTUMBUHAN TANAMAN GAHARU (Aquilaria malaccensis Lamk) PADA TANAH ALUVIAL DENGAN NAUNGAN DAN TINGGI BIBIT BERBEDA - Usuluddin, .; Burhanuddin, .; Muin, Abdurrani (Universitas Tanjungpura, 2018)
Agarwood (Aquilaria malaccensis Lamk) includes a restricted type of plant and its trade as an effort to conserve germplasm from the threat of extinction. Semi-tolerant silviculture of agarwood-tolerant at the level of seedlings that require shade, causing the community can not grow agarwood in open land. High seed information and light intensity (shading) that provides the best growth and survival are required for successful ex-situ cultivation of this species, especially in open alluvial soils. The purpose of this study was to determine the intensity of shade and height of agarwood seeds above 60 cm which is the best growth in open alluvial soil. The research used a randomized factorial design with 2 factors that is high seed factor, consisting of 3 treatment levels (60-70 cm, 80-90 cm and 100 cm above) and shade factor, consisting of 3 treatment levels (0%, 60% and 70%). The number of treatment combinations was 9 and each treatment was repeated 5 times. The results showed that the gaharu seeds planted (height 60 cm and above), able to grow in open alluvial soil with 100% live percentage. Agarwood seeds with height above 100 cm, have higher height and better diameter than small size seedlings, either with shade (60%) or without shade (0%), although not statistically significant. The result of soil fertility analysis showed that the soil in the research location is not fertile, so this condition is expected to influence the growth of agarwood plant that is tested besides the light intensity factor.Kata kunci :Â Â Agarwood, alluvial soil, growth, high of seedlings, shade intensity, vitality.